Lipid Raft, Regulator of Plasmodesmal Callose Homeostasis - Iswanto, Arya Bagus Boedi (Plants (Basel), 2017)
The specialized plasma membrane microdomains known as lipid rafts are enriched by sterols and sphingolipids. Lipid rafts facilitate cellular signal transduction by controlling the assembly of signaling molecules and membrane protein trafficking. Another specialized compartment of plant cells, the plasmodesmata (PD), which regulates the symplasmic intercellular movement of certain molecules between adjacent cells, also contains a phospholipid bilayer membrane. The dynamic permeability of plasmodesmata (PDs) is highly controlled by plasmodesmata callose (PDC), which is synthesized by CALLOSE SYNTHASES (CalS) and degraded by β-1,3-GLUCANASES (BGs). In recent studies, remarkable observations regarding the correlation between lipid raft formation and symplasmic intracellular trafficking have been reported, and the PDC has been suggested to be the regulator of the size exclusion limit of PDs. It has been suggested that the alteration of lipid raft substances impairs PDC homeostasis, subsequently affecting PD functions. In this review, we discuss the substantial role of membrane lipid rafts in PDC homeostasis and provide avenues for understanding the fundamental behavior of the lipid raft–processed PDC.